Beneath the light [videorecording (DVD)] - Baumgartner, John, 1971-; Seng, Cindy Davis; Charles, Jonathan; Tinker, Zach; Pyper-Ferguson, John; Chavez, Ana Nicolle; Sitawi, Kieran (Vision Films, 2025)
A young man with a haunted past takes a job repairing an abandoned lighthouse reachable only by boat. When the surly owner leaves him there alone, his feelings of isolation and uneasiness grow. He begins to see the strange apparition of a young girl that he can't understand how he recognizes, forcing him to come to grips with the mistakes of his past or risk losing his sanity forever.